Viruses affecting lentil in Jordan - A.N. MANSOUR, O. AL- MABROUK and (Indian Phytopathology, 2002)
In a survey during in 1995-96, 3 viruses were identified from 400 lentil leaf samples, and 1 was identified from lentil seeds collected from the main growing regions in Jordan. The viruses were identified as alfalfa mosaic alfamovirus, bean yellow mosaic potyvirus, broad bean stain comovirus (BBSV) and pea seed-borne mosaic potyvirus (PSBMV). BBSV and PSBMV were seed transmitted up to 2.1% and 0.8%, respectively, in all the tested commercial cultivars of lentil. The highest disease incidence (16.5%) occurred in Rabba at the end of the growing season. BBSV was the most prevalent virus, followed by PSBMV. This is thought to be the first report of viruses affecting lentils in Jordan.